2019
DOI: 10.1093/jpepsy/jsz084
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Illness Stigma, Health Communication Difficulties, and Thwarted Belongingness to Depressive Symptoms in Youth with Inflammatory Bowel Disease

Abstract: Objective Youth with inflammatory bowel disease (IBD) often experience difficulties communicating about their disease. It is suspected that the stigmatizing nature of IBD symptoms contributes to youths’ health communication difficulties, leaving youth feeling disconnected from their social environment and potentially resulting in decreased social belongingness and poorer emotional functioning. In this study, we tested an illness stigma → health communication difficulties → thwarted belongingn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Unlike the children studied at NIH, the scores of older FD/MAS patients indicated worse QOL than pediatric patients with Asthma [6]. Worse scores on psychosocial components of the PEDS-QL in adolescents with FD/MAS than children with other chronic diseases may reflect the difficulty of managing physical symptoms of a rare condition that sets them outside age group norms without a supportive identity community [30]. Craniofacial differences, in particular, may result in difficult interactions, negative emotions, and a need to manage a stigmatic identity [31].…”
Section: Discussionmentioning
confidence: 87%
“…Unlike the children studied at NIH, the scores of older FD/MAS patients indicated worse QOL than pediatric patients with Asthma [6]. Worse scores on psychosocial components of the PEDS-QL in adolescents with FD/MAS than children with other chronic diseases may reflect the difficulty of managing physical symptoms of a rare condition that sets them outside age group norms without a supportive identity community [30]. Craniofacial differences, in particular, may result in difficult interactions, negative emotions, and a need to manage a stigmatic identity [31].…”
Section: Discussionmentioning
confidence: 87%
“…While our qualitative study suggests the presence of, and motivations for, concealment among adolescents with chronic pain in the context of pain-related stigma, future research should examine in what context or relationships adolescents with chronic pain may feel comfortable disclosing their health status or symptoms. The decision to seek support from others has been studied in other populations with concealable stigmas ( Barned et al, 2016 ; Roberts et al, 2020 ) and pediatric chronic conditions ( Barned et al, 2016 ). The decision to disclose health status can vary based on situational contexts, which creates challenges in the measurement of stigma concealment due to its existence along a continuum ( Pihlaskari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to disclose health status can vary based on situational contexts, which creates challenges in the measurement of stigma concealment due to its existence along a continuum ( Pihlaskari et al, 2020 ). Further, it is important to note that communicating about disclosure of chronic medical conditions can be challenging even with less stigmatizing conditions ( Roberts et al, 2020 ), and the role of communication difficulties related to one’s health status may be a contributing factor in lack of disclosure ( Remedios and Snyder, 2018 ; Puhl et al, 2019 ). A greater understanding of these communication barriers in adolescents with chronic pain may lead to appropriate interventions to improve communications and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…IBD nondisclosure due to embarrassment is also a reported problem in the literature [13,26], but, because concealment of any condition is associated with reduced engagement with others [28], feelings of disconnection and negative affect are likely to be high among those with IBD because of social problems as much as they are to do with disease severity. Indeed, recent work by Roberts, Gamwell et al [29] showed that difficulty communicating about their illness to others was associated with thwarted belonging that was also linked to higher depression. Thus, where stigmatised beliefs are internalised to become part of one's identity, there are potential impacts on mental health [28]: feeling ashamed of one's self because of their IBD is likely to increase feelings of disconnection and depression.…”
Section: Risk Factors For Poor Mental Health Among Aya With Ibdmentioning
confidence: 99%